La participación en la sociología: elementos para una praxis sociológica - Ganuza Fernández, Ernesto (Política y Sociedad, 2007)
The contemporary sociology has renewed the mainstream of sociology. Almost every book of referente in the field of sociology written the last twenty five years has interpreted and changed the core elements to talk about society and social relations. For this respect, it has been stressed the importance of reflexive agents and contingent conditions to explain sociological matters, so it has lowered the importance of structural features. The new scenario opened by sociological theory, even with its differences and contradictions, does not seem to have reached the empirical sociology, where we can still find the image of an agent far away of reflexive references. The propose of the paper is to bring the discussion to empirical field to evaluate the contributions made by participatory methodologies about this issue.